Pengaruh Penerapan Akuntansi Terhadap Kinerja Keuangan Riot Vape Store di Sragen Tahun 2025 - Alip Prihanto; Susilaningtyas Budiana Kurniawati; Supartini Supartini (Masyarakat Ekonomi Syariah Bogor, 2026)
This study aims to analyze the implementation of simple accounting and its effect on the financial performance of Riot Vape Store in Sragen. The research employed a qualitative approach using interviews, observations, and documentation as data collection techniques. The informants consisted of the business owner and employees who are directly involved in daily operations and financial recording activities. The collected data were analyzed by comparing field findings with relevant accounting and financial management theories. The results show that Riot Vape Store has implemented simple accounting practices through daily cash records, monthly recapitulation using Microsoft Excel, and the preparation of a simple income statement. These accounting practices assist the business owner in understanding cash flow, controlling operational costs, managing inventory, and evaluating the overall financial performance of the business. Although the accounting system is still manual and has not fully complied with the Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM), it has provided significant benefits in maintaining profit stability and business continuity. The study also reveals that simple accounting practices contribute to greater transparency and improved managerial decision-making. Therefore, simple accounting plays an essential role in supporting financial performance and sustainability of micro and small enterprises, particularly in the retail sector.